2012
DOI: 10.1016/j.ijhm.2011.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Doing good to do well? Corporate social responsibility reasons, practices and impacts in small and medium accommodation enterprises

Abstract: Corporate social responsibility practices have been mostly analyzed in the large manufacturing business context, with little attention paid to the service sector and even less to small and medium-sized tourism enterprises. This study aims to fill this gap through analyzing how these enterprises take responsibility. A survey of nearly 400 enterprises showed that the main reason for acting responsibly is altruistic, arising from the managers and owners' values and lifestyle. Sustainability measures have a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
291
1
52

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(369 citation statements)
references
References 74 publications
25
291
1
52
Order By: Relevance
“…Research remains largely inconclusive with regards to a positive relationship between CSR and CFP (Lee, 2008) and this is especially the case for the service sector and small enterprises (Garay & Font, 2012).…”
Section: Generic Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…Research remains largely inconclusive with regards to a positive relationship between CSR and CFP (Lee, 2008) and this is especially the case for the service sector and small enterprises (Garay & Font, 2012).…”
Section: Generic Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…The authors concluded that CSR activities would improve the tourism enterprises' financial performance. Garay and Font (2012) maintained that businesses that take sustainability actions for eco-savings reasons perform best financially. On the other hand, the authors contended that the businesses that take sustainability actions for moral reasons are happy with their financial performance.…”
Section: Kirkmentioning
confidence: 99%
“…Since the concept of CSR is new in business sector especially in the hotel industry [13,14]; it is not considered as a large company and lacked an extensive research works But it has a good position to practice corporate social responsibility whatever the sizes it [15]. Especially in the workplace/ employee any business organization needs to be addressed.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Especially in the hotel industry CSR is gaining ground; possibly because hotels are of manageable size, and committed hotels can achieve a lot. Many writers (Garay and Font [15]; Inoue and Lee [16]; Baltruschat [17]; Argandona [18]; Efiong [19]) indicated that hotel industry in the tourism industry is the best actor for the achievement of corporate social responsibility ideology in their business practice.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation